2013
DOI: 10.1371/journal.pone.0066267
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Adipose Tissues Reveals that ECM-Receptor Interaction Is Involved in the Depot-Specific Adipogenesis in Cattle

Abstract: Adipocytes mainly function as energy storage and endocrine cells. Adipose tissues showed the biological and genetic difference based on their depots. The difference of adipocytes between depots might be influenced by the inherent genetic programing for adipogenesis. We used RNA-seq technique to investigate the transcriptomes in 3 adipose tissues of omental (O), subcutaneous (S) and intramuscular (I) fats in cattle. Sequence reads were obtained from Illumina HiSeq2000 and mapped to the bovine genome using Topha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 75 publications
4
78
0
Order By: Relevance
“…The findings of the present study indicated that the DEG ITGB6 in DCM was significantly enriched in the ECM-receptor interaction pathway. Notably, ECM-receptor interaction is also involved in DCM pathway (35). Thus, it can be inferred that ECM-receptor interaction may be an important pathway for DCM, which may be altered by the integrin gene ITGB6.…”
Section: Itga11 Col6a1 Lamc2mentioning
confidence: 99%
“…The findings of the present study indicated that the DEG ITGB6 in DCM was significantly enriched in the ECM-receptor interaction pathway. Notably, ECM-receptor interaction is also involved in DCM pathway (35). Thus, it can be inferred that ECM-receptor interaction may be an important pathway for DCM, which may be altered by the integrin gene ITGB6.…”
Section: Itga11 Col6a1 Lamc2mentioning
confidence: 99%
“…ECM‐receptor interaction is reportedly related to adipose tissue (Lee et al . 2013). These results indicate that these variants may be the reason for enhanced fat deposition in these Chinese indigenous pigs.…”
mentioning
confidence: 99%
“…Most of our samples obtained reads in excess of 30 Mbp. Many studies have already shown that reads of around 30 Mbp were adequate in detecting 90% of annotated genes in cattle, and chicken (Lee et al, 2013;Li et al, 2011;Wang et al, 2011). These references suggest that our data had sufficient coverage, even though the tissue used for this study was different from that of previous studies.…”
Section: Sequencing Quality and Coveragementioning
confidence: 71%
“…EdgeR provided Cox-Reid profile methods to estimate the dispersion for the pairwise comparisons between control and T1, control and T2, control and T3, T1 and T2, T1 and T3, and T2 and T3 dietary treatment groups. The remaining Cox-Reid common volume dispersion methods were followed as published in our earlier study (Lee et al, 2013). In this study, important DEGs for each pairwise comparison were selected at FDR of 0.01.…”
Section: Statistical Analysis and Deg Identificationmentioning
confidence: 99%
See 1 more Smart Citation